Quando o mundo é o começo: o papel da internacionalização na formação e operação de born digitals - Mello, Jéssica Sara Vasconcelos (2026)
This dissertation investigates how Born Digital companies are conceptualized in the academic literature and how digital internationalization participates in the formation of these organizations. The dissertation is structured around two complementary articles: the first conducts a systematic literature review, following the PRISMA 2020 protocol, to organize definitions, characteristics, and conceptual tensions of the Born Digital phenomenon; the second develops a case study of a North American fintech to analyze how digital and international resources are orchestrated during the pre-formation and organizational emergence phase. The findings demonstrate that digital internationalization is not a subsequent stage of expansion, but a constitutive element of the very process of creating digital firms. Theoretically, the study integrates the literatures on Born Digitals, organizational emergence, and resource orchestration within a unified analytical framework. Methodologically, it articulates systematic review and qualitative case study in a complementary approach. Managerially, it offers guidance for founders to structure digital platforms from the outset in globally connected and regulatorily bounded contexts, in alignment with Sustainable Development Goals 8 and 9.